Effect of goethite coating on the Nuclear Magnetic Resonance relaxation signal in sand - Duschl, Markus; Pohlmeier, Andreas; Vereecken, Harry (Diffusion Fundamentals, 2013)
Nuclear magnetic resonance relaxation is a fast and well-known method to get a measure of pore size distributions. To obtain reliable results, one needs to get information about influences like internal gradients evoked by paramagnetic impurities on the NMR relaxation signal. Therefore, we did a series of longitudinal and transverse relaxation experiments of samples with variable paramagnetic content. Missing echo time and magnetic field strength dependence leads us to the conclusion that we have no significant influence of internal gradients in our measurements.